Towards Data-Driven Teaching Strategies to Develop Mathematical Thinking - Gao, Yaqi; Yuan, Rui; Li, Jiansheng (Enthusiastic : International Journal of Applied Statistics and Data Science, 2022)
Mathematics learning is not only about learning knowledge but also about cultivating mathematical thinking and learning how to think about and solve mathematical problems. Unfortunately, the way teachers evaluate students is still based on the student’s academic achievement. Many students learn by rote, which is unsuitable for developing their thinking ability at different levels. With the advent of the era of big data, teaching has become more accurate and convenient. In this paper, we analyze the student’s academic performance at different levels from the point of view of mathematical thinking. We collected the learning achievement of two classes in a middle school in Beijing. We then analyzed the overall thinking of the two classes, and the mathematical thinking level of students at different levels. Based on the analysis results, we put forward some teaching suggestions on improving mathematical thinking to help improve teaching methods and quality and promote students’ mathematical thinking development.